1998
DOI: 10.1101/gad.12.6.831
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila myb is required for the G2/M transition and maintenance of diploidy

Abstract: The myb proto-oncogenes are thought to have a role in the cell division cycle. We have examined this possibility by genetic analysis in Drosophila melanogaster, which possesses a single myb gene. We have described previously two temperature-sensitive, recessive lethal mutants in Drosophila myb (Dm myb). The phenotypes of these mutants revealed a requirement for myb in diverse cellular lineages throughout the course of Drosophila development. We now report a cellular explanation for these findings by showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 56 publications
(94 reference statements)
11
63
0
Order By: Relevance
“…A further argument for a unique function of B-Myb is provided by recent work on Drosophila melanogaster. Drosophila has a single myb gene (Dm-myb) that has been implicated in cell proliferation and in controlling the activity of certain origins of DNA replication (Katzen et al, 1998;Beall et al, 2002;Fitzpatrick et al, 2002). Recent work has shown that B-myb, but not A-myb or c-myb, is able to complement a defective Dm-myb gene (Davidson et al, 2004), suggesting a unique and probably ancestral function for B-myb, which cannot be complemented by other vertebrate myb family members.…”
Section: Discussionmentioning
confidence: 99%
“…A further argument for a unique function of B-Myb is provided by recent work on Drosophila melanogaster. Drosophila has a single myb gene (Dm-myb) that has been implicated in cell proliferation and in controlling the activity of certain origins of DNA replication (Katzen et al, 1998;Beall et al, 2002;Fitzpatrick et al, 2002). Recent work has shown that B-myb, but not A-myb or c-myb, is able to complement a defective Dm-myb gene (Davidson et al, 2004), suggesting a unique and probably ancestral function for B-myb, which cannot be complemented by other vertebrate myb family members.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these mutants (KW606AA and DQ617AA) were capable of rescuing weakly at 18°C when expressed via the native Myb promoter, implying that these mutant proteins themselves are heat-sensitive. Interestingly, the heat-sensitive hypomorphic Myb 1 mutant has a single amino acid substitution in the same highly conserved animal-specific region of the protein (G613S) (34) (Fig. 1).…”
Section: Evolutionarily Guided Alanine Substitution Mutants Of Drosopmentioning
confidence: 99%
“…In contrast to vertebrates, a single myb gene has been found in Drosophila (10). The dm-myb gene regulates the G 2 ͞M transition, maintains normal ploidy and spindle formation, and plays a role in DNA synthesis (11)(12)(13)(14)(15). Interestingly, recent evidence has shown that knockdown of human B-myb leads to a reduction of cyclin B and cdc2 expression, suggesting that mammalian B-myb may be involved in G 2 ͞M regulation as well (16).…”
mentioning
confidence: 99%